Elevated Lipoprotein(a) levels increase Major Adverse Limb Event. (3rd October 2022) - Guedon, A; De Freminville, J B; Mirault, T; Mohamedi, N; Rance, B; Fournier, N; Paul, J L; Messas, E; Goudot, G
Abstract: Background: High lipoprotein(a) levels are involved in the development of cardiovascular events, as particularly in myocardial infarction, stroke, and peripheral artery disease. Studies assessing prognostic values of lipoprotein(a) levels on the lower limbs are lacking. Purpose: The aim of our study was to look after a relationship between the lipoprotein(a) level and the incidence of major adverse limb events (MALE) defined as major amputation, peripheral artery endovascular revascularization or peripheral artery bypass. Methods: We included 16, 513 patients with lipoprotein(a) measurements from our clinical information system. Normal lipoprotein(a) level was under 50 mg/dL and we defined: high lipoprotein(a) level as a lipoprotein(a) level between 50 mg/dL and 134 mg/dL and very high lipoprotein(a) level as a lipoprotein(a) levels over 134 mg/dL, i.e the 95th percentile in this cohort. Accelerated Failure Time models were used to assess the relationship between the lipoprotein(a) level and the incidence of MALE retrieved from the patient's electronic record during a median (interquartile range) follow-up of 3.74 (1.07; 7.30) years after the lipoprotein(a) measurement. MALE was defined as the occurrence of one of the following during follow-up: aortofemoral bypass surgery, limb bypass surgery, percutaneous transluminal angioplasty revascularization of the iliac, or infrainguinal arteries; or major amputation above the forefoot. Secondary outcomes included individual components of the primary Results: Median lipoprotein(a) level was 24 mg/dL (10; 60), with 70.3%; 24.7%; and 5.0% within normal; high and very high lipoprotein(a) level respectively. The 1-year MALE incidence was 2.2% [95% CI: 1.96; 2.51]; 2.60% [95% CI: 2.09; 3.10] and 4.54% [95% CI: 3.08; 5.98] among the normal, high and very high lipoprotein(a) level patients respectively. High and very high lipoprotein(a) levels were independently associated with an increased risk of MALE (adjusted Accelerated Failure Time Exponential Estimate) 0.43 [95% CI: 0.24; 0.78], p=0.01 and 0.17 [95% CI: 0.07; 0.40], p<0.001, respectively. Conclusion: In this large cohort of unselected real-world hospital inpatients, higher lipoprotein(a) levels were independently associated with an increased risk of MALE. Though, lipoprotein(a) measurement shall be taken into account not only to refine the cardiovascular risk but also the lower limb risk of revascularization or amputation. Funding Acknowledgement: Type of funding sources: None.